Influencing Factors of Organizational Citizenship Behavior (OCB) Among Civil Servants (PNS) In Organization X - Endah Sri Lestari; Sri Muliati Abdullah (Publikasi Indonesia, 2025)
Organizational Citizenship Behavior (OCB) has an important role in the success and effectiveness of an organization, including: improving organizational work, increasing job satisfaction, building a positive work culture, improving the organization's work image, and encouraging innovation and positive change. This research uses a case study design because the main research problem is the analysis of OCB in employees in an organization and because this design is a more appropriate strategy when it comes to why something happened. This research aims to describe the factors that influence Organizational Citizenship Behavior (OCB) in Civil Servants in Organisasi X. The type of research used by researchers is descriptive qualitative research. Based on the results of observations and interviews, Organizational Citizenship Behavior (OCB) implemented by Civil Servants (PNS) in Organization These factors have a positive relationship with OCB, which is directly proportional to the increase in OCB as per the research results described above. The relationship between employees (superiors and subordinates) is very good as can be seen from the attitudes and behavior applied in work life. Even though OCB is not yet fully implemented by all employees, there are ongoing improvement efforts to achieve organizational goals. Subordinates carry out their duties as they should and superiors carry out monitoring and evaluation to ensure activities run smoothly. Obstacles that arise in carrying out tasks are immediately conveyed to superiors and/or related units so that they can be followed up immediately so that no work is missed. As for corrections to a job, they will be carried out with full responsibility based on previous experience.